2018
DOI: 10.3168/jds.2017-12890
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Genomic prediction using imputed whole-genome sequence variants in Brown Swiss Cattle

Abstract: The accuracy of genomic prediction determines response to selection. It has been hypothesized that accuracy of genomic breeding values can be increased by a higher density of variants. We used imputed whole-genome sequence data and various single nucleotide polymorphism (SNP) selection criteria to estimate genomic breeding values in Brown Swiss cattle. The extreme scenarios were 50K SNP chip data and whole-genome sequence data with intermediate scenarios using linkage disequilibrium-pruned whole-genome sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 18 publications
2
35
0
Order By: Relevance
“…The impact of imputation accuracy on genomic selection accuracy was studied by several authors. The genotype densification allowed to increase the genomic evaluation accuracy depending on the architecture of evaluated traits [65,66]. Moreover, genomic selection accuracy increased with better imputation accuracies [26,28].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of imputation accuracy on genomic selection accuracy was studied by several authors. The genotype densification allowed to increase the genomic evaluation accuracy depending on the architecture of evaluated traits [65,66]. Moreover, genomic selection accuracy increased with better imputation accuracies [26,28].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we identified 9 interesting genes controlling fertility on BTA17. Frischknecht et al (2018) found a QTL region for nonreturn rate at d 56, and the interval from first to last insemination on BTA8 in Brown Swiss cattle. Liu et al (2017) reported strong associations with conception rate at first insemination and the interval to first insemination in Chinese and Nordic Holstein cows on BTA23 and for heifers on BTA17.…”
Section: Discussionmentioning
confidence: 90%
“…Contrary to those ndings, our study showed no signi cant increase in prediction accuracy when using WGS variants as opposed to SNP from the HD. Other authors have also observed lower or no signi cant bene ts in predictive ability gain using sequence data comparing with SNP arrays [6,9,10,12,45,49,50].…”
Section: Predictive Abilitymentioning
confidence: 98%